Global mesozooplankton communities show lower connectivity in deep oceanic layers - Oriol Canals; Jon Corell; Ernesto Villarino; Guillem Chust; Eva Aylagas; Iñaki Mendibil; Craig T. Michell; Juan Ignacio González‐Gordillo; Xabier Irigoien; Naiara Rodríguez‐Ezpeleta (Molecular Ecology, 2024)
Mesozooplankton is a key component of the ocean, regulating global processes such as the carbon pump, and ensuring energy transfer from lower to higher trophic levels. Yet, knowledge on mesozooplankton diversity, distribution and connectivity at global scale is still fragmented. To fill this gap, we applied DNA metabarcoding to mesozooplankton samples collected during the Malaspina‐2010 circumnavigation expedition across the Atlantic, Indian and Pacific oceans from the surface to bathypelagic depths. We highlight the still scarce knowledge on global mesozooplankton diversity and identify the Indian Ocean and the deep sea as the oceanic regions with the highest proportion of hidden diversity. We report no consistent alpha‐diversity patterns for mesozooplankton at a global scale, neither across vertical nor horizontal gradients. However, beta‐diversity analysis suggests horizontal and vertical structuring of mesozooplankton communities mostly attributed to turnover and reveals an increase in mesozooplankton beta‐diversity with depth, indicating reduced connectivity at deeper layers. Additionally, we identify a water mass type‐mediated structuring of mesozooplankton bathypelagic communities instead of an oceanic basin‐mediated as observed at upper layers. This suggests limited dispersal at deep ocean layers, most likely due to weaker currents and lower mixing of water mass types, thus reinforcing the importance of oceanic currents and barriers to dispersal in shaping global plankton communities.

Evaluation of the global marine mesozooplankton diversity using alternative metabarcoding approaches - Corell Jon; Aylagas Eva; Michell Craig; González-Gordillo J.Ignacio; Irigoien Xabier; Rodriguez-Ezpeleta Naiara (Frontiers in Marine Science, 2016)